EXPONENTIAL DECAY OF THE WEAK SOLUTION OF A NONLINEAR WAVE EQUATION - Santiago Ayala, Yolanda Silvia (2005)
In this article, we prove the existence and uniqueness of the weak solution of a nonlinear wave equation. We prove the uniqueness by using the Visik - Ladyshenkaia Method. Also, using the Nakao s Lemma, we prove the exponential decay ofthe energy associated to the system.